Co‐prescription of low‐dose methotrexate and trimethoprim‐sulfamethoxazole and the 30‐day risk of death among older adults: A cohort study - Sadeghi, Hasti; Ahmadi, Fatemeh; McArthur, Eric; Sontrop, Jessica M.; Abdullah, Sheikh S.; Urquhart, Brad L.; Kim, Richard B.; Muanda, Flory T. (British journal of clinical pharmacology, 2025)
Aims The aim of this study was to characterize the risk of death in older adults co‐prescribed low‐dose methotrexate and TMP‐SMX vs. low‐dose methotrexate and a cephalosporin. Methods We conducted a retrospective, population‐based, new‐user cohort study in Ontario, Canada (April 1, 2002–August 1, 2022) using linked administrative healthcare data. Older adults taking low‐dose methotrexate who were newly co‐prescribed TMP‐SMX (n = 1602) were matched 1:1 with those who were newly co‐prescribed a cephalosporin. The primary outcome was death within 30 days of the antibiotic dispensing date. Secondary outcomes included all‐cause hospitalization, a hospital visit with myelosuppression and a hospitalization with persistent infection defined as the main diagnosis. Propensity score matching was used to balance comparison groups on indicators of baseline health. Risk ratios (RR) were obtained using modified Poisson regression. Results In a propensity‐score matched cohort of 3204 adults taking low‐dose methotrexate, the 30‐day risk of death was similar in adults co‐prescribed TMP‐SMX vs. a cephalosporin (14/1602 [0.87%] vs. 15/1602 [0.94%]; RR 0.93 [95% CI 0.45–1.93]). The risk of all‐cause hospitalization (RR 1.49 [95% CI 1.13–1.97]) and infection (RR 2.78 [95% CI 1.30–5.95]) was higher in adults treated with TMP‐SMX than those treated with cephalosporins. Conclusions In older adults taking low‐dose methotrexate, co‐prescription of TMP‐SMX vs. a cephalosporin was not associated with a higher 30‐day risk of death but was associated with a higher 30‐day risk of all‐cause hospitalization and hospital admission with persistent infection. If verified, these risks should be balanced against the benefits of co‐prescribing TMP‐SMX and low‐dose methotrexate.